Development of a Seismic Vulnerability Assessment Risk Map - Amiri, Sara (2011)
Earthquake is one of the disasters which can cause problems to the economy and the society. Based on historical seismic data, Tehran has suffered from several strong earthquakes with a return period of 150 years. The local seismologists are considering the possibility of a large earthquake in Tehran in the near future because there have not been any large earthquakes in the past 170 years. Since most data related to earthquake have spatial properties, GIS can be used as an effective tool for managing and decision making in disaster time. In some countries such as Iran, disaster experiences show that managing and making decisions right before the occurrence of an earthquake are more effective than doing something after it has taken place. Therefore, planning an action in pre-disaster phases in the disaster management cycle is much more important. Hence, one of the crucial phases in disaster management cycle, known as mitigation, is specifically meant for creating a resistant city against earthquake. In this study, three steps were used to evaluate vulnerable urban fabrics. The first step was adapted using seismic, geological criteria and suitability matrix to identify buildings that are exposed to danger. Meanwhile, a simplified index was used in the second step for the identification of buildings that would block roads when earthquakes took place. The third step was developed to evaluate recovery areas on the basis of division of city framework for escape and relief people. The results illustrate almost 80% of the total residential buildings are located in high risk site and unsuitable locations. The high amount of building demolition which could cause road blockage and delays in rescues and relief operation had been detected. Some problem caused by shortage of land or space for evacuation and emergency response.The findings of this study reveals that effective risk maps for management and reduction seismic disaster are necessary. In addition, the issues of preparedness, emergency response activities, seismic retrofit and recovery actions and policies shall also be taken into consideration.